Social Learning in One-Arm Bandit Problems. - Rosenberg, Dinah; Solan, Eilon; Vieille, Nicolas (Econometrica, 2007)
We study a two-player one-arm bandit problem in discrete time, in which the risky arm can have two possible types, high and low, the decision to stop experimenting is irreversible, and players observe each other's actions but not each other's payoffs. We prove that all equilibria are in cutoff strategies and provide several qualitative results on the sequence of cutoffs. Reprinted by permission of the publisher.